Patient-related factors and outcome of retinoblastoma in Calabar, Nigeria: A single-center, retrospective study - Elizabeth D. Nkanga; Anthony C. Nlemadim; Mattan Arazi; Dennis G. Nkanga; Roseline E. Duke; Ido D. Fabian; Essemfon D. Nkanga; Friday A. Odey; Martin M. Meremikwu (Elsevier, 2024)
Background: Retinoblastoma is associated with mortality in resource-poor nations due to disparities and poor access to treatment. The aim was to determine the relationships between patient-related factors and clinical outcomes of retinoblastoma in a tertiary hospital in Nigeria. Material and methods: It was a retrospective study of all children diagnosed and treated for retinoblastoma from January 2017 through December 2022. Information obtained from their records included bio-socioeconomic data, symptoms, lag time from initial symptoms, staging, treatment, and survival outcome. Results: Fifty-three patients, aged 6-88 months on first hospital presentation were recruited. There were 29 (54.7%) females. Twenty (37.7%) patients died. The majority were the last child of their parents (62.3%) with a low socioeconomic class (86.8%) and lived in rural areas (50.9%). The median (interquartile) age at diagnosis [24 (18-36) months, p = 0.005] and lag time [13 (6-20) months, p = 0.274] were lower in those who survived than in those who died. The prevalence of bilateral disease (20.8%, p = 0.002), brain metastasis (22.6%, p < 0.001), stage IV disease (18.9%, p = 0.01) and relapse (34%, p < 0.001) was higher among the patients who died. The median (interquartile) overall survival (OS) was 22 (11.8-32.2) months with a 1-year OS of 63%. Treatment with only chemotherapy [HR 4.76 (95% CI: 1.7-13.1)], incomplete chemotherapy [HR 5.61 (95% CI: 1.3-24.7)], relapse [HR 5.98 (95% CI: 1.4-25.9)] and eye surgery delayed after 3 chemotherapy cycles [HR 8.22 (95% CI: 1.1-62.2)] were predictors of mortality. Conclusion: Most patients with retinoblastoma arrived at our treatment center approximately 14 months following the first symptom. Most (84.9%) presented with proptosis. The majority were of a low social class (86.8%), had a secondary level of education only (47.2%), and lived in rural areas (50.9%). The 3-year overall survival was 29%.